L‐carnitine supplementation for muscle weakness and fatigue in children with neurofibromatosis type 1: A Phase 2a clinical trial. Issue 10 (21st June 2021) - Vasiljevski, Emily R.; Burns, Joshua; Bray, Paula; Donlevy, Gabrielle; Mudge, Anita J.; Jones, Kristi J.; Summers, Matthew A.; Biggin, Andrew; Munns, Craig F.; McKay, Marnee J.; Baldwin, Jennifer N.; Little, David G.; et al.
Abstract: Reduced muscle tone, muscle weakness, and physical fatigue can impact considerably on quality of life for children with neurofibromatosis type 1 (NF1). Human muscle biopsies and mouse models of NF1 deficiency in muscle show intramyocellular lipid accumulation, and preclinical data have indicated that L‐carnitine supplementation can ameliorate this phenotype. The aim of this study is to examine whether daily L‐carnitine supplementation is safe and feasible, and will improve muscle strength and reduce fatigue in children with NF1. A 12‐week Phase 2a trial was conducted using 1000 mg daily oral levocarnitine tartrate supplementation. Recruited children were between 8 and 12 years old with a clinical diagnosis of NF1, history of muscle weakness and fatigue, and naïve to L‐carnitine. Primary outcomes were safety (self‐reporting, biochemical testing) and compliance. Secondary outcomes included plasma acylcarnitine profiles, functional measures (muscle strength, long jump, handwriting speed, 6‐minute‐walk test [6MWT]), and parent‐reported questionnaires (PedsQL™, CBCL/6–18). Six children completed the trial with no self‐reported adverse events. Biochemical tests for kidney and liver function were normal, and the average compliance was 95%. Plasma acylcarnitine levels were low, but within a range not clinically linked to carnitine deficiency. For strength measures, there was a mean 53% increase in dorsiflexion strength (95% confidence interval [CI] 8.89–60.75; p  = 0.02) and mean 66% increase in plantarflexion strength (95% CI 12.99–134.1; p  = 0.03). In terms of muscle performance, there was a mean 10% increase in long jump distance (95% CI 2.97–16.03; p  = 0.01) and 6MWT distance (95% CI 5.88–75.45; p  = 0.03). Comparison with the 1000 Norms Project data showed a significant improvement in Z‐score for all of these measures. Parent reports showed no negative impact on quality of life, and the perceived benefits led to the majority of individuals remaining on L‐carnitine after the study. Twelve weeks of L‐carnitine supplementation is safe and feasible in children with NF1, and a Phase 3 trial should confirm the efficacy of treatment.